AMS 14C Dating Problem and High-Resolution Geochemical Record in Manzherok Lake Sediment Core From Siberia: Climatic and Environmental Reconstruction for Northwest Altai Over the Past 1,500 Years - Blyakharchuk, Tatiana; Udachin, Valerii; Li, Hong-Chun; Kang, Su-Chen (Frontiers in Earth Science, 2020)
This study presents high-resolution multi-proxy biological and geochemical records in an 82-cm sediment core from Manzherok Lake located in forest-steppe zone on western piedmonts of Altai Mountain, Russia. Based on 210Pb dating and 48 AMS 14C dates as well as pollen data and geochemical proxies, detailed lake history and local climatic changes over the 1500 years are obtained. Prior to Medieval Warm Period (MWP), the lake had high productivity under stable moderately wet and warm conditions. During 1150~1070 yr BP, strong surface runoff led to high detritus input and increasing lake level, reflecting onset of MWP. The lake was deep and fresh under warm and wet conditions of MWP (1070~ 850 yr BP). In this interval, more aquatic algae and submerged plants on the lake bottom were generated, which would use dissolved CO2 partially decomposed from organic matters in the deeper sediment layers. Consequently, many ABA treated samples contain old carbon influence on their 14C dates. This calls for attention on chronological construction of lake sediments. During 850~700 yr BP, the lake level started to drop with reduced sediment load under cooling and drying conditions. Low sedimentation and lake productivity occurred due to cold and dry climates during 700~500 yr BP. Very low sedimentation and hiatus were attributed to ice cover and weak water input between 500 and 50 yr BP corresponding to cold and dry Little Ice Age. Manzherok Lake has recovered productivity and deposition during the current warming century. Change in the total solar irradiance (TSI) is an important factor to influence climate in the Altai Mountains. With decreased TSI, Siberian High became strong, which led to Westerly and polar front be pushed away from this region, resulting arid climates. The situation was reversed vice versa.